Technological culture as a basis for technological capabilities and learning - Carvajal Villaplana, Álvaro (2012)
In this work a positive correlation is supposed to exist between  technological capabilities and  a technological culture. Promoting a technological culture favors the  emergence and development of  technological capabilities in a given culture. We analyze here three approaches  to the notion of technological culture:  (a) epistemological, (b) descriptive and (c) prescriptive.  We  consider also a  special kind  of technological capability:  that of innovation.